PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN OCB TERHADAP KINERJA KARYAWAN DENGAN MEDIASI KOMITMEN ORGANISASI PADA PT. BPR JAYA KERTI - Putra, Kadek Mahendra; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen, 2016)
This study aimed at analyzing the effect of transformational and OCB leadership on employee performance with organizational commitment mediation. This research was conducted at PT. BPR Jaya Kerti. Sampling of this study made use census method with 46 employees of PT. BPR Jaya Kerti. The data were collected through interviews and questionnaires. Data analysis techniques applied in this research was the analysis of the path. The results of the study showed that; 1) transformational leadership had positive and significant effect on organizational commitment, 2) the transformational leadership showed positive and significant effect on employee performance, 3) the OCB indicated positive and significant effect on organizational commitment, 4) the OCB had positive and significant effect on employee performance, 5) organizational commitment and significant showed positive effect on employee performance.
Keywords: Kepemimpinan transformasional, OCB, Komitmen Organisasi, Kinerja Karyawan